Delayed gastric emptying in the obese: an assessment using the non-invasive (13)C-octanoic acid breath test. - Jackson, S; Leahy, F; McGowan, A; Bluck, L; Coward, W; Jebb, SA (2004)
AIM: Much of the controversy surrounding the correlation between obesity and gastric emptying lies in the inconsistency of methodology and analysis. This study was designed to overcome some of the discrepancies encountered in previous studies and to test the hypothesis that obese individuals have altered gastric emptying compared to lean individuals. METHODS: Gastric emptying was measured using the (13)C-octanoic acid breath test in 16 lean and 16 obese women pair-matched for age. Following an overnight fast, subjects were given a standard 2 MJ egg meal labelled with 100 microl of [1-(13)C]-octanoic acid. Breath samples were collected at regular intervals over a 6-h period. (13)C-isotopic enrichment in the breath was analysed using isotope ratio mass spectrometry and the data fitted to the established gastric emptying model. The lag times (t(lag)), half excretion times (t(1/2)), latency phase (t(lat)) and ascension times (t(asc)) were calculated. RESULTS: The mean t(1/2)-values (+/-standard error of the mean) were 3.67 +/- 0.14 h and 4.23 +/- 0.18 h for lean and obese respectively, indicating significantly delayed gastric emptying in the obese (p = 0.019). The obese group also showed a significantly slower lag time (t(lag), p = 0.005) and latency phase (t(lat), p = 0.005), but no significant difference was found in the ascension time (t(asc), p = 0.154). Within groups, no correlation was found between half excretion times and body weight or half excretion times and body mass index. CONCLUSIONS: The present study demonstrated a prolonged lag phase and delayed gastric emptying in obese women when compared to lean women. This delay may be as a consequence of high-fat diets, a sedentary lifestyle and increased gastric distension associated with obesity, or a contributing factor in the pathogenesis of obesity resulting from the inactivation of gastrointestinal satiety signals and in an increase in food intake.